2020
DOI: 10.1002/cpt.1998
|View full text |Cite
|
Sign up to set email alerts
|

A Microdose Cocktail to Evaluate Drug Interactions in Patients with Renal Impairment

Abstract: Renal impairment (RI) is known to influence the pharmacokinetics of nonrenally eliminated drugs, although the mechanism and clinical impact is poorly understood. We assessed the impact of RI and single dose oral rifampin (RIF) on the pharmacokinetics of CYP3A, OATP1B, P‐gp, and BCRP substrates using a microdose cocktail and OATP1B endogenous biomarkers. RI alone had no impact on midazolam (MDZ), maximum plasma concentration (Cmax), and area under the curve (AUC), but a progressive increase in AUC with RI sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
73
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(84 citation statements)
references
References 39 publications
(114 reference statements)
9
73
1
Order By: Relevance
“…Additionally, as MDZ is an intermediate hepatic extraction drug, a physiological reduction of hepatic blood flow anticipated in the elderly might also contribute to the observed reduction in hepatic clearance of MDZ (Dundee et al, 1986;Amrein and Hetzel, 1990). Our finding that CKD was not associated with changes in pharmacokinetic profiles of MDZ was consistent with a previous study where neither AUC nor C max of MDZ was affected by renal impairment (Tatosian et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, as MDZ is an intermediate hepatic extraction drug, a physiological reduction of hepatic blood flow anticipated in the elderly might also contribute to the observed reduction in hepatic clearance of MDZ (Dundee et al, 1986;Amrein and Hetzel, 1990). Our finding that CKD was not associated with changes in pharmacokinetic profiles of MDZ was consistent with a previous study where neither AUC nor C max of MDZ was affected by renal impairment (Tatosian et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…The cocktail drugs include 1) midazolam (MDZ), a specific and selective substrate for CYP3A; 2) dabigatran etexilate (DABE), a selective substrate for intestinal P-gp; 3) pitavastatin (PTV), a relatively selective substrate for OATP1B; 4) rosuvastatin (RSV), a substrate of BCRP and OATP1B; and 5) atorvastatin (ATV), a substrate of CYP3A, OATP1B, BCRP, and P-gp. This cocktail was subsequently studied in patients with CKD, and the study results suggested that CKD reduces intestinal P-gp and BCRP activity (Tatosian et al, 2020). However, whether the observed changes were due solely to CKD or as a consequence of advancing age, remains inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Simulated decreased AUCR in 521CC is consistent with data reported with clinical OATP1B probes 3,6 and suggests the risk of underestimation of the magnitude of transporter-mediated interaction if these subjects are included in a CPI-drug interaction study, which is more likely to happen in clinical studies performed without prior genotyping (e.g., first-in-human study) or in populations with higher prevalence of 521CC. 48 In contrast, any changes in CPI synthesis did not affect fraction transported via OATP1B and simulated AUCR, highlighting no risk of underestimation of the OATP1B interaction magnitude if female subjects are included in the study. As exemplified here, the modeling of CPI gives us prospective insights of clinical output and enables optimal clinical design to increase likelihood of success.…”
Section: Prospective Application Of the Developed Cpi Modelmentioning
confidence: 89%
“…As exemplified here, the modeling of CPI gives us prospective insights of clinical output and enables optimal clinical design to increase likelihood of success. Furthermore, the physiological description of the liver processes in the CPI model enables the extension of the model to other special populations (e.g., evaluation of the changes in OATP1B activity in the chronic kidney disease population) 49,50 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation